Biomarkers and Their Possible Functions in the Intestinal Microenvironment of Chagasic Megacolon: An Overview of the (Neuro)inflammatory Process - José Rodrigues do Carmo Neto; Yarlla Loyane Lira Braga; Arthur Wilson Florêncio da Costa; Fernanda Hélia Lucio; Thais Cardoso do Nascimento; Marlene Antônia dos Reis; Mara Rubia Nunes Celes; Flávia Aparecida de Oliveira; Juliana Reis Machado; Marcos Vinícius da Silva (Journal of Immunology Research)
The association between inflammatory processes and intestinal neuronal destruction during the progression of Chagasic megacolon is well established. However, many other components play essential roles, both in the long-term progression and control of the clinical status of patients infected with Trypanosoma cruzi. Components such as neuronal subpopulations, enteric glial cells, mast cells and their proteases, and homeostasis-related proteins from several organic systems (serotonin and galectins) are differentially involved in the progression of Chagasic megacolon. This review is aimed at revealing the characteristics of the intestinal microenvironment found in Chagasic megacolon by using different types of already used biomarkers. Information regarding these components may provide new therapeutic alternatives and improve the understanding of the association between T. cruzi infection and immune, endocrine, and neurological system changes.